Khung phân tích sử dụng học liệu số trong dạy học ở trường phổ thông theo tiếp cận CIPO - Du, Nhat; Nguyễn Như Quỳnh Anh, Nguyễn Như Quỳnh Anh (Tạp chí Giáo dục, 2026)
In the context of educational digital transformation and the implementation of the 2018 General Education Curriculum, digital learning resources have become an important pedagogical resource for renewing teaching activities in general schools. This article systematizes theoretical issues and proposes a CIPO-based analytical framework for the use of digital learning resources in teaching. The findings clarify the concept, role, requirements, and types of digital learning resources, and define their use as teachers’ process of selecting, designing, adapting, organizing the exploitation of, and evaluating digital learning resources to support students’ learning tasks and competence development. The proposed framework identifies Context and Input as enabling conditions, Process as the core pedagogical sequence of teacher actions, and Output as learning and teaching outcomes.